2014
DOI: 10.1371/journal.pone.0088887
|View full text |Cite
|
Sign up to set email alerts
|

Importin 7 and Nup358 Promote Nuclear Import of the Protein Component of Human Telomerase

Abstract: In actively dividing eukaryotic cells, chromosome ends (telomeres) are subject to progressive shortening, unless they are maintained by the action of telomerase, a dedicated enzyme that adds DNA sequence repeats to chromosomal 3′end. For its enzymatic function on telomeres, telomerase requires nuclear import of its protein component (hTERT in human cells) and assembly with the RNA component, TERC. We now confirm a major nuclear localization signal (NLS) in the N-terminal region of hTERT and describe a novel on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 51 publications
(83 reference statements)
2
23
0
Order By: Relevance
“…6B). As a positive control for the method we also confirmed that importin 7 coimmunoprecipitated with hTERT-GFP (data not shown), as this interaction had been reported previously (Frohnert et al, 2014). Finally, we used importin 4 as a negative control, since knockdown of cellular levels of importin 4 had no effect on TRα1 localization.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…6B). As a positive control for the method we also confirmed that importin 7 coimmunoprecipitated with hTERT-GFP (data not shown), as this interaction had been reported previously (Frohnert et al, 2014). Finally, we used importin 4 as a negative control, since knockdown of cellular levels of importin 4 had no effect on TRα1 localization.…”
Section: Resultssupporting
confidence: 89%
“…The GFP-glutathione-S-transferase (GST)-GFP (G3) expression vector, G3- A/BD (containing NLS-2) expression plasmid, and G3-Hinge (containing NLS-1) expression plasmid were previously described (Mavinakere et al, 2012). The plasmid hTERT-GFP was a gift from R. H. Kehlenbach (University of Göttingen) and encodes GFP-tagged human telomerase reverse transcriptase (Frohnert et al, 2014). pGST-GFP-NLS was a gift from R. J.G.…”
Section: Methodsmentioning
confidence: 99%
“…Importin 7 has been recently shown to interact with hTERT and to mediate nuclear transport of hTERT (Frohnert et al, 2014). To confirm these results in our system, we examined whether importin 7 binds to the hTERT NLS, and whether its depletion affects the levels and subcellular localization of hTERT and telomerase activity.…”
Section: Discussionsupporting
confidence: 61%
“…Thus, it is of interest to investigate whether phosphorylation of S227 affects the interaction between the hTERT NLS and the import receptors. Recently, importin 7 has been shown to interact with the hTERT NLS and to mediate nuclear transport of hTERT (Frohnert et al, 2014). However, the molecular mechanism regulating the nuclear import of hTERT remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanism of hTERT uptake and presentation to CD4 T cells had been poorly studied. Indeed, few studies were focused on hTERT presentation on MHC-II mainly due to the inability to produce recombinant hTERT protein (14)(15)(16). Recently, Kellermann et al (17) described a method to produce recombinant hTERT protein.…”
mentioning
confidence: 99%